The role of steroid hormones and chemical carcinogen benzo(a)pyrene in premature rupture of membranes in preterm pregnancy - N V Artimuk; N N Elizarova; E G Polenok (IP Berlin A.V., 2017)
The aim of this study was to investigate the levels of estradiol, progesterone; antibodies Ig classes A and G to them and to benzo(a)pyrene in women with premature rupture of membranes (PROM) at 22-36.6 weeks of gestation and in women without PROM in the same period. A retrospective, comparative, analytical study was taken. The study included 149 patients, group 1 consisted of women with PROM at 22-36.6 weeks of gestation (n=68), group 2 - women with a normal pregnancy without PROM at 22-36.6 weeks of gestation (n=81). Isotype differences in the formation of antibodies (Ig) to estradiol were revealed in women from group I compared with group II. High level of IgA antibodies to estradiol is more common in women with PROM at 22-36.6 weeks of gestation.